Post-Marxism : a reader - Sim, Stuart (Edinburgh University Press, 1998)
This is the first source-book for the cross-disciplinary area. It takes students through a wide range of readings from philosophy, politics, and sociology, to human geography, international relations, and feminist studies. Bringing together statesments from leading twentieth-century thinkers such as Derrida, Lyotard, Baudrillard, and Laclau and Mouffe, and with the editor's substantial introduction, this is an ideal teaching text, inspiring debate about the future of Marxism as a cultural theory.